Prognostic impact of KRAS, NRAS, BRAF, and PIK3CA mutations in primary colorectal carcinomas: a population-based study. Issue 1 (December 2016) - Palomba, Grazia; Doneddu, Valentina; Cossu, Antonio; Paliogiannis, Panagiotis; Manca, Antonella; Casula, Milena; Colombino, Maria; Lanzillo, Annamaria; Defraia, Efisio; Pazzola, Antonio; Sanna, Giovanni; Putzu, Carlo; et al.
Abstract Background Activation of oncogenes downstream the EGFR gene contributes to colorectal tumorigenesis and determines the sensitivity to anti-EGFR treatments. The aim of this study was to evaluate the prognostic value ofKRAS, BRAF, NRAS andPIK3CA mutations in a large collection of CRC patients from genetically-homogeneous Sardinian population. Methods A total of 1284 Sardinian patients with histologically-proven diagnosis of colorectal carcinoma (CRC) and presenting with metastatic disease were included into the study. Genomic DNA was isolated from formalin-fixed, paraffin-embedded primary tumour tissue samples of CRC patients and screened for mutations inRAS andBRAF genes, using pyrosequencing assays, and inPIK3CA gene, using automated DNA sequencing assays. Results Overall, mutation rates were 35.6 % forKRAS, 4.1 % forNRAS, and 2.1 % forBRAF . Among available DNA samples, 114/796 (14.3 %) primary CRCs were found to carry a mutation in thePIK3CA gene. In this subset of patients analysed in all four genes, a pathogenetic mutation of at least one gene was discovered in about half (378/796; 47.5 %) of CRC cases. A mutatedBRAF gene was found to steadily act as a negative prognostic factor for either time to progression as metastatic disease (from detection of primary CRC to diagnosis of first distant metastasis; p = 0.009) or partial survival (from diagnosis of advanced disease to the time of death or last control; p = 0.006) or overall survival (p < 0.001). No significant impact on prognosis was observed for mutatedKRAS, NRAS, andPIK3CA genes or combinedRAS mutations (allRAS ). Conclusions Our study defines both prevalence and prognostic role of main activated oncogenes in a population-based large collection of CRC patients.